Vanmanenia maculata, a new species of hillstream loach from the Chang-Jiang Basin, South China (Teleostei: Gastromyzontidae) - Yi, Wen-Jing; Zhang, E; Shen, Jian-Zhong (Zootaxa, 2014)
Vanmanenia maculata, new species, is described from the middle and lower Chang-Jiang basin in Hubei, Hunan, and Jiangxi provinces, South China. This new species, along with V. caldwelli, V. stenosoma, and V. striata, is distinguished from all other Chinese species of the genus by lacking secondary rostral barbels. It is distinct from V. caldwelli and V. striata in anus placement, rostral lobule shape, and body coloration, and from V. stenosoma in having a larger scaleless area on the ventral surface of the body and a shallower caudal-peduncle. Vanmanenia polylepis should be removed from the synonymy of V. pingchowensis and regarded as valid.